The Eternity of God: Richard Swinburne vs. Thomas Aquinas - Ozioko, Johnson Uchenna (Alpha Omega, 2023)
One of the fundamental properties which theism has always attributed to God is eternity. However, when it comes to spelling out what it effectively means to claim that God is eternal, different theists seem to part ways in their construal of this essential divine attribute. Whereas the classical Christian view which goes back to Origen, Augustine, Boethius, St. Anselm, and St. Thomas has interpreted God’s eternity in terms of timelessness, that is, His being outside time, a contrary view which understands God’s eternity in terms of His being everlasting has been tenaciously espoused in more recent time by the renowned contemporary natural theologian, Richard Swinburne. By this, Swinburne implies that God is not outside time but is rather in every time that ever was, is and will be; He is backwardly and forwardly everlasting. Inasmuch as both views seem persuasive, this essay evaluates the position of Swinburne vis-à-vis the classical view more critically as represented in the thought of St. Thomas Aquinas. Through a critical analysis of both positions and an exposition of their fundamental differences, strengths and weaknesses, it examines which interpretation helps better clearing the shadow enshrouding the question of God’s eternity.